MO332THE IRRADIATION-INDUCED RENAL ISCHEMIC PRECONDITIONING IS BLUNTED BY THE ORAL ADMINISTRATION OF THE ANTI-ANGIOGENIC AGENT, SUNITINIB. (29th May 2021) - Khbouz, Badr; Lallemand, François; Rowart, Pascal; Poma, Laurence; Noel, Agnès; Krzesinski, Jean-Marie; Sounni, Nor Eddine; Jouret, François
Abstract: Background and Aims: Whole-body irradiation has been suggested to induce renal ischemic preconditioning (RIP) in rodent models, possibly via neo-angiogenesis. First, we comprehensively investigate the pathways involved in kidney-centered irradiation. Next, we assess the functional and structural impact of kidney-centered irradiation applied before ischemia/reperfusion (I/R) injury. Finally, we test whether Sunitinib-mediated inhibition of the neo-angiogenesis prevents irradiation-associated RIP. Method: Experiment 1: Unilateral irradiation of the left kidney (8.56 Gy) was performed in male 10-week-old wild-type C57bl/6 mice (n=10). One month later, total kidney RNA was extracted from irradiated and control (n=5) mice for comparative high-throughput RNA-Seq (using BaseSpace Sequence Hub Illumina). Functional enrichment analysis was performed using Database for Annotation, Visualization and Integrated Discovery (DAVID). Experiment 2: Two x-ray beams (225Kv, 13mA) specifically targeted both kidneys for a total dose of 8.56Gy. The right kidneys were removed and harvested, and the left kidneys undergo 30-minute ischemia followed by 48-hour reperfusion (n=8) at Days 7-14-21-28 post irradiation. Experiment 3: Following the same protocol of renal I/R at Day14, 3 groups of male 10-week-old wild-type C57bl/6 mice were compared (n=8 per group): 1/ bilateral pre-irradiation; 2/ bilateral pre-irradiation and gavage with Sunitinib from Day2 to Day13; 3/ control group without irradiation or gavage. Results: Experiment 1: Comparative transcriptomics showed a significant up-regulation of various signaling pathways, including angiogenesis ( HMOX1 ) and stress response ( HSPA1A, HSPA1B ). Expressions of angiogenesis markers (CD31, TGFb1, HMOX1) showed an increase at both mRNA (real-time qPCR) and protein (immuno-staining) levels in irradiated kidneys compared to controls (p<0.01). Experiment 2: Following I/R, the blood urea nitrogen (BUN) and serum creatinine (SCr) levels were significantly lower in the irradiated animals compared to controls: (BUN: 86.2±6.8 vs. 454.5±27.2mg/dl; SCr: 0.1±0.01 vs. 1.7±0.2mg/dl, p<0.01). The renal infiltration by CD11b-positive cells (187±32 vs. 477±20/mm²) and F4-80 macrophages (110±22 vs. 212±25/mm²) was significantly reduced in the irradiated group. The real-time qPCR mRNA levels of the angiogenic markers, TGFb1 and CD31, were significantly increased in the irradiated group compared to controls (p<0, 01). The CD31-immunostating (quantified by FiJi) was increased in irradiated mice compared to controls (p<0.01). Experiment 3: One-way analysis of variance followed by Tukey's test showed that, following I/R, the serum levels of BUN and SCr were lower in irradiated group compared to controls (BUN: 106.1±33.6 vs. 352.2±54.3mg/dl; SCr: 0.3±0.13 vs. 1±0.2mg/dl), and in irradiated group compared to the irradiated-exposed group to Sunitinib (BUN: 106.1±33.6 vs. 408.4±54.9mg/dl; SCr: 0.3±0.12 vs. 1.5±0.3mg/dl; p<0.01). No difference was observed between the irradiated-exposed mice to Sunitinib and the controls. Conclusion: Renal irradiation induces the activation of signaling pathways involved in angiogenesis in mice. Renal pre-irradiation leads to RIP, with preserved renal function and attenuated inflammation post I/R. Exposure to the anti-angiogenic drug Sunitinib post-irradiation prevents the irradiation-induced RIP.